A case study on the early stage of Pinus nigra invasion and its impact on species composition and pattern in Pannonic sand grassland - Bakacsy László; Szepesi Ágnes (2024)
Alien woody species are successful invaders, frequently used for afforestation in regions like semi-arid lands. Shrubs and trees create important microhabitats in arid areas. Understorey vegetation in these habitats has unique species composition and coexistence. However, the impact of solitary woody species on understorey vegetation is less understood. This study evaluated the effect of native ( Juniperus communis ) and invasive solitary conifers ( Pinus nigra ) on surrounding vegetation, where individuals were relatively isolated (referred to as solitary conifers). The field study conducted in Pannonic dry sand grassland in 2018 recorded plant and lichen species presence around six selected solitary conifers. Composition and pattern of understorey vegetation were assessed using 26 m belt transects with 520 units of 5 cm × 5 cm contiguous microquadrats. Compositional diversity (CD) and the number of realized species combinations (NRC) were calculated from the circular transects. Results showed native conifer J. communis created more complex, organized microhabitats compared to alien P. nigra . CD and NRC values were significantly higher under native conifers than invasive ones ( p = 0.045 and p = 0.026, respectively). Native species also had more species with a homogeneous pattern than the alien species. Alien conifers negatively affected understorey vegetation composition and pattern: some species exhibited significant gaps and clusters of occurrences along the transects under P. nigra . Based on our study, the removal of invasive woody species is necessary to sustain habitat diversity.
Keywords: Biológiai tudományok